Reindeer (Rangifer tarandus tarandus) feeding on lichens and mushrooms: traditional ecological knowledge among reindeer-herding Sami in northern Sweden - Inga, Berit (Rangifer, 2009)
The study was performed in four reindeer-herding districts (Sami villages) in northern Sweden. Reindeer herding Sami, born in 1950 or earlier, were interviewed about reindeer foraging behaviour on lichens and mushrooms, especially relating to non-summer grazing habits, and about characteristics of a good winter feeding ground. The informants claimed that lichens are preferably grazed in the wintertime, but that they also may be eaten in the summertime when the weather is cold and humid. Mushrooms were chosen in the autumn months August and September, but according to some informants mushrooms may also be eaten during late autumn (from Oct.) when frozen and under the snow. The reindeer herders had different names for lichens, which in general terms describe their appearance and habitat. For mushrooms they only used one Sami name. Ground lichens preferred by reindeer are Cladonia species, while the nitrogen-fixing lichen species such as Nephroma arcticum and Stereocaulon pascale were said not to be preferred by the reindeer. Snow conditions are very important, and the less snow (and the softer it is), the better. Habitats where reindeer herders know from experience that snow conditions tend to be problematic, e.g. in moist and open areas with small trees, are used early in the winter (Oct.–Jan.), before too much snow has accumulated. A good winter grazing area should have lichens. It is preferably a dry pine (Pinus sylvestris) forest heath with large, old and wide-crowned trees to shelter the ground from snow and thereby ease the cratering by reindeer. Abstract in Swedish / Sammanfattning: Renens (Rangifer tarandus tarandus) bete av lavar och svampar: Traditionell ekologisk kunskap bland renskötande samer i norra Sverige Studien genomfördes i fyra renskötseldistrikt (samebyar) i norra Sverige. Totalt 22 renskötande samer, födda 1950 eller tidigare, blev intervjuade om renens betande av lavar och svampar, renens vinterbete och om vad som karaktäriserar ett bra vinterbetesland. Informanterna hävdade att lavar företrädesvis betas under vintern, men även kan betas under sommaren då vädret är kallt och fuktigt. Svampar betas under höstmånaderna augusti och september, men enligt några informanter kan svamp även betas senare på hösten (från oktober) när den är frusen och under snön. Renskötarna har namn på lavar som i generella termer beskriver deras utseende och växtplats. För svampar använder de enbart ett samiskt namn, guoppar. Av de marklevande lavarna ansåg informanterna att renarna föredrar Cladonia-arter (renlavar), medan kväve-fixerade arter som Nephroma arcticum (norrlandslav) och Stereocaulon pascale (påskrislav) inte ansågs föredras av renarna. Snöförhållandena är mycket viktiga, och ju mindre snö (och ju lösare den är) desto bättre. Växtplatser där renskötarna vet av erfarenhet att snöförhållandena kan bli problematisk, t.ex. i fuktiga och öppna områden med små träd, används till bete tidigt under vintern (oktober-januari) innan för mycket snö har fallit. Ett bra vinterbetesområde ska ha gott om lavar. Det bästa är en torr tallhed (Pinus sylvestris) med stora och gamla träd med vida kronor som fångar upp snön som upplega och på det viset skyddar marken från snö, vilket gör det lättare för renarna att gräva.